2021
DOI: 10.3390/molecules26092690
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of D‒α‒Tocopheryl Polyethylene Glycol Succinate‒block‒Poly(ε-Caprolactone) (TPGS−b−PCL) Nanocarriers for Solubilization and Controlled Release of Paclitaxel

Abstract: The objective of this study was to synthesize and characterize a set of biodegradable block copolymers based on TPGS-block-poly(ε-caprolactone) (TPGS-b-PCL) and to assess their self-assembled structures as a nanodelivery system for paclitaxel (PAX). The conjugation of PCL to TPGS was hypothesized to increase the stability and the drug solubilization characteristics of TPGS micelles. TPGS-b-PCL copolymer with various PCL/TPGS ratios were synthesized via ring opening bulk polymerization of ε-caprolactone using T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…A previous study reported that naringenin exhibited absorption peaks of O-H stretching vibration at 3285 cm -1 and C=O stretching vibration at 1629 cm -1 (29). PEG and TPGS were shown to exhibit hydroxyl groups at 3417 cm -1 and 3452-3454 cm -1 , respectively (11,30). The characteristics band for the C=O stretching vibration of carbonyl group appeared at 1630 cm -1 for PEG (30) and at 1737-1738 cm -1 for TPGS (11).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…A previous study reported that naringenin exhibited absorption peaks of O-H stretching vibration at 3285 cm -1 and C=O stretching vibration at 1629 cm -1 (29). PEG and TPGS were shown to exhibit hydroxyl groups at 3417 cm -1 and 3452-3454 cm -1 , respectively (11,30). The characteristics band for the C=O stretching vibration of carbonyl group appeared at 1630 cm -1 for PEG (30) and at 1737-1738 cm -1 for TPGS (11).…”
Section: Discussionmentioning
confidence: 89%
“…Drug encapsulation within micelles core can be achieved through electrostatic, physical or chemical interactions (5). Different types of co-polymer such as poly(ethylene glycol) (PEG), poly(ε-caprolactone) (PCL), and D-α-tocopheryl polyethylene glycol 1000 succinate (TPGS) have been studied in the formulation of cancer drug-loaded PMs (10,11). It is noteworthy that PMs are able to enhance drug bioavalability and biodistribution (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Self-assembled nanocarriers composed of D-αtocopheryl poly(ethylene glycol) succinate-block-poly(εcaprolactone) (TPGS-b-PCL) and loaded with paclitaxel owe their properties to PEG, which extends their circulation time, and vitamin E, that enhances the cellular uptake of the medication. 54 The TPGS, which is a derivative of the natural vitamin E (α-tocopherol) conjugated with PEG, was also used as a component for the production of micelles containing docetaxel. 55 Among the advanced delivery systems, tested both in vitro and in vivo, one can mention pH-sensitive, multidrug (α-tocopherol and doxorubicin) grafted O-carboxymethyl chitosan polymeric micelles with chemically conjugated targeting ligand (anti-HER2/neu peptide-PEG).…”
Section: Copolymer Micellesmentioning
confidence: 99%
“…Currently, most conventional chemotherapeutic agents (e.g., Adriamycin (DOX), methotrexate, and camptothecin) have serious disadvantages that need to be addressed, such as low selectivity, low water solubility, substantial side effects, and short circulation time in the body [ 2 , 3 ]. To overcome these problems, scientists have developed a range of nanocarriers, such as nanoparticles, liposomes, nanogels and micelles through nanotechnology [ 4 , 5 , 6 , 7 , 8 ], such as nanocarrier-based polymer prodrugs. The hydrophobic segments of the polymer are linked to the hydrophobic drug by breakable chemical bonds to form the core of the micelle, and the hydrophilic segments form the micelle shell, providing good stability to the drug and prolonging the circulation time in vivo.…”
Section: Introductionmentioning
confidence: 99%